HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PENGGUNAAN SWAMEDIKASI OBAT PADA PENDERITA PENYAKIT KULIT DI DESA RUGEMUK KECAMATAN PANTAI LABU KABUPATEN DELI SERDANG TAHUN 2024 - Parera, Geby; Sinaga , Lia Rosa Veronika; Manurung, Jasmen; Hasibuan, Eva Kartika (Akupun Tour Publisher, 2024)
Background: Skin disease is one of the seven largest types of directly infectious diseases in Indonesia. Skin diseases which are generally considered harmless and do not result in death are often ignored by society. Purpose: The aim of this research is to determine the relationship between knowledge and attitudes with the use of self-medication drugs in skin disease sufferers in Rugemuk village, Pantai Labu sub-district, Deli Serdang district in 2024. Methods: The type of research is quantitative research with a cross-sectional research design approach with a population of 80 samples and using total population techniques. . Primary data collection was carried out directly through questionnaires and secondary data was obtained from Regemuk village. The results of univariate analysis show that the majority of people's knowledge level is good (61.3%), the majority of people's attitude variables are good (87.5%), and the majority of self-medication drugs are in the good category (77.5%).. Disscusion and Conclusion: The results of the hypothesis test show that there is a relationship between the level of knowledge and the use of drug self-medication in Rugemuk Village, Pantai Labu District, Deli Regency with a value of p=0.007 (p<0.05). The results of the hypothesis test show that there is a relationship between attitudes and the use of drug self-medication in Rugemuk Village. Pantai Labu District, Deli Regency with a value of p=0.008 (p<0.05). This research recommends that the community health center provide education and counseling to the public regarding drug self-medication, so that the public can know what is permitted and not permitted in carrying out drug self-medication measures, so as to increase knowledge and attitudes about drugs for drug self-medication measures.